Pengaruh Kemampuan Berpikir Kritis dan Berpikir Logis Siswa Terhadap Kemampuan Belajar Secara Kolaboratif Pada Jurusan Teknik Komputer dan Jaringan di SMK Negeri 2 Malang - Fariatul Auniyah; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
This research was performed with a purpose to know the effect of students critical thinking on collaborative learning and students logical thinking on collaborative learning. This research method is a quantitative method that will produce numbers to be processed, the design in this research is expost facto design. The sample used in this study there were 75 students with students characters being same are. In this research data collection performed with distributing questionnaires by online (Online). For data processing in this study the study used a simple linear regression test and partial testing (T- test). Results from this research is (1) critical thinking skills have an influence on students learning abilities in a collaborative manner, this is evidenced by the calculation results showing a significance value of 0.014 < 0.05, (2) logical thinking skills not have an influence on learning abilities collaboratively, this is evidenced by the calculation results showing a value of significance is 0.416 > 0.005